Knowledge of medication dispensing among community pharmacists in Brazil: A national cross-sectional survey - João Paulo Alves Cunha; João Paulo Vilela Rodrigues; Kérilin Stancini Santos Rocha; Ana Maria Rosa Freato Gonçalves; Fabiana Rossi Varallo; Leoanardo Régis Leira Pereira (PLoS ONE, 2025)
Brazilian community pharmacists’ knowledge of medication dispensing was assessed through a nationally representative cross-sectional survey conducted between October 2021 and May 2022. A total of 366 licensed pharmacists working in private community pharmacies—71.3% of whom were female, with an average age of 36.4 years (standard deviation 9.4)—completed a validated online questionnaire covering fundamental aspects of dispensing practice and reported on their undergraduate training and preferred information sources. The overall mean correct-response rate was 70.8%, with the Southeast and South regions scoring highest at 71.0% and 71.9%, respectively. Domains related to antimicrobial and over-the-counter medication dispensing exhibited the largest knowledge gaps across all regions. Graduates of public universities and pharmacists holding postgraduate qualifications demonstrated significantly greater proficiency, and higher knowledge scores correlated with more positive perceptions of the relevance of their training for patient counseling and community health promotion. Internet resources and medication package inserts were the most frequently consulted references for resolving dispensing questions, with 38% of respondents consulting them on a daily basis. These findings reveal a moderate overall level of dispensing competence, pinpoint critical areas for improvement, and underscore the influence of educational background on professional performance. Targeted continuing-education initiatives are therefore essential to reinforce pharmacists’ competencies, enhance the quality of services in community pharmacies, and ultimately improve patient care outcomes.